Signatures of mitonuclear coevolution in a warbler species complex - Silu Wang (Nature Portfolio, 2021)
Little is known on how mitonuclear interactions influence genomic divergence among hybrid and parental lineages. A study of hybridizing wood warbler species complex finds a nuclear gene block with mitochondrial functions coevolves with mitochondrial genome, driven by climate-associated divergent selection underlying hybrid-parental population divergence.